1990
DOI: 10.1136/oem.47.7.442
|View full text |Cite
|
Sign up to set email alerts
|

Blood lead concentration, renal function, and blood pressure in London civil servants.

Abstract: Blood lead concentration was measured in 398 male and 133 female London civil servants not subject to industrial exposure to heavy metals. The relation between blood lead and serum creatinine concentrations and blood pressure were examined. Blood lead concentration ranged from 0-20 to 1-70 pmol/l with a geometric mean concentration of 0-58 umolIl in men and 0-46 pmol/l in women (p < 0-001). In women blood lead concentration increased with age (r = + 0-27; p = 0 002). In the two sexes blood lead concentration w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 22 publications
1
37
2
Order By: Relevance
“…This concurs with the conclusion drawn in a recent comprehensive review. 5 This study is the first to use a nationally representative sample of the English population whereas previous studies in the UK have investigated age-sexrestricted 9,10 or occupational 11 subgroups of the population, and the results of these studies were inconsistent and conflicting.…”
Section: Discussionmentioning
confidence: 98%
“…This concurs with the conclusion drawn in a recent comprehensive review. 5 This study is the first to use a nationally representative sample of the English population whereas previous studies in the UK have investigated age-sexrestricted 9,10 or occupational 11 subgroups of the population, and the results of these studies were inconsistent and conflicting.…”
Section: Discussionmentioning
confidence: 98%
“…Among drinkers (n = 1068) the median ethanol intake was 18.4 g/day and more than 90% of total alcohol intake was due to wine. With regard to smoking habits, 72% of subjects were nonsmokers; among current smokers (369 subjects) the median consumption was of 15 cigarettes daily (25th-75th centiles: [8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Resultsmentioning
confidence: 99%
“…Grandjean et al (12) observed that the positive relationship between B-Pb and blood pressure was no longer significant when alcohol intake and hemoglobin were included in a multiple regression analysis. Staessen et al (13) reported that the addition of gender and age as covariates to models predicting blood pressure reduced the partial correlations of systolic and diastolic blood pressure with B-Pb to a nonsignificant level. Sharp et al (6) observed that a positive relationship between blood pressure and B-Pb was present in black males but not among nonblack males; the inclusion of alcohol use indicators in multiple regression models did not alter the relationship between blood pressure and B-Pb by more than 10%.…”
Section: Introductionmentioning
confidence: 99%
“…Levels in men are usually somewhat higher than in women (10). B-Pb also norn~ally increases with age (1 1, 12).…”
Section: Samplingmentioning
confidence: 99%